Design and construction of a manually operated castorbean-cum-sunflower seed dehuller. - Hussain, A. A. M.; Sabur, M. A.; Rahman, M. M. (1980)
A description of the design and construction of a manually operated seed dehuller suitable for castor and sunflower seeds is presented. The unit, which is entirely constructed from locally available materials, consists of a hopper, a rotary drum feeder and two horizontal rubber faced dehulling discs. Tests have indicated that at optimal speed the hulling capacity is 0.45 kg/min, with a hulling quality of 60% for castor and 70% for sunflower seed.